2021
DOI: 10.3390/biom11020336
|View full text |Cite
|
Sign up to set email alerts
|

Actin Cytoskeleton and Regulation of TGFβ Signaling: Exploring Their Links

Abstract: Human tissues, to maintain their architecture and function, respond to injuries by activating intricate biochemical and physical mechanisms that regulates intercellular communication crucial in maintaining tissue homeostasis. Coordination of the communication occurs through the activity of different actin cytoskeletal regulators, physically connected to extracellular matrix through integrins, generating a platform of biochemical and biomechanical signaling that is deregulated in cancer. Among the major pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 214 publications
(170 reference statements)
0
25
0
Order By: Relevance
“…We have recently shown that MASTL regulates actin stress fiber formation and cell contractility in a kinase-independent manner by promoting MRTF-A/SRF-mediated transcription of actomyosin-related genes ( Taskinen et al., 2020 ). Dysregulation of cell contractility and TGF-β signaling is associated with cancer ( Melchionna et al., 2021 ). Interestingly, TGF-β has been shown to trigger nuclear translocation of MRTF-A and -B which coordinately regulate transcription of Slug, a well-known inducer of EMT with SMAD3 ( Morita et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that MASTL regulates actin stress fiber formation and cell contractility in a kinase-independent manner by promoting MRTF-A/SRF-mediated transcription of actomyosin-related genes ( Taskinen et al., 2020 ). Dysregulation of cell contractility and TGF-β signaling is associated with cancer ( Melchionna et al., 2021 ). Interestingly, TGF-β has been shown to trigger nuclear translocation of MRTF-A and -B which coordinately regulate transcription of Slug, a well-known inducer of EMT with SMAD3 ( Morita et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…With TGF-β1 treatment, the F-actin filamentous structures became longer and more extended. 44 Quantitative image analysis of the live/dead results revealed high percentages of viable cells (>89%) under all four conditions throughout the 14 days of culture (Figure 3C), confirming the cytocompatiblity of the bioorthogonal hydrogel platform.…”
Section: Secm Supports the Growth Of Vocal Fold Fibroblasts In 3dmentioning
confidence: 99%
“…When α and β subunit cytoplasmic tails bind to the salt bridge and ligands bind to the binding sites, the extracellular domain changes from a bent conformation to a highly extended conformation, thereby enhancing the binding affinity of integrins to ligands [ 31 , 32 ] ( Figure 2 ). Cells maintain dynamic cell–ECM contact by modulating cytoskeleton filaments and their connections with transmembrane proteins [ 33 ]. The cytoskeleton, a key cellular component, is composed of a system of filaments that includes microtubules, microfilaments, and intermediate filaments.…”
Section: Overview Of β2 Integrinsmentioning
confidence: 99%